Influence of the Meaning of Work on the Life Satisfaction of Confucian Ministers in Indonesia - Andre William; Yusak Novanto (Program Studi Ilmu Agama Islam Program Magister, Universitas Islam Indonesia, 2023)
â€œLife satisfactionâ€ is an individualâ€™s cognitive assessment of the quality of their life. One factor that influences life satisfaction is the meaning of work. The â€œmeaning of workâ€ is a personâ€™s broad perspective of his work. This study investigates whether there is a significant effect of the meaning of work on the life satisfaction of Confucian ministers in Indonesia. This quantitative research was conducted with a linear regression research design on 81 active Confucian ministers throughout Indonesia. The measurement tools used in this study are the Work as Meaning Inventory (WAMI) to measure the meaning of work and the Riverside Life Satisfaction Scale (RLSS) to measure life satisfaction. The results of this study found that the meaning of work had a significant effect of 18.4% on the life satisfaction of Confucian ministers. In addition, it was also found that the dimension of meaning-making through work has the greatest influence on life satisfaction. Based on these results, it is suggested that leaders of Confucian ministers to make better regulations for their organizations to improve the life satisfaction of their ministers by focusing on their perceived meaning of work.